1994
DOI: 10.1136/ard.53.9.614
|View full text |Cite
|
Sign up to set email alerts
|

An immunogenetic study of familial scleroderma.

Abstract: Objective-To study the role of the HLA system in the genetic susceptibility to familial systemic sclerosis (SSc). Methods-HLA class I antigens were determined by classic serological methods and HLA-DRB, -DQA and -DQB genes were analysed by genetic typing in 36 individuals belonging to two families with several individuals affected by SSc. Results-The results did not show any association of the inheritance to SSc with any particular HLA allele in these families but revealed a striking frequency of ANA autoantib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Unexpectedly, a higher frequency of ANA in the healthy spouses of the patients (50%) and other members of both families, compared with the ANA prevalence in their first‐degree relatives (19%), was shown. Also, these results could account for the existence of environmental exposure shared by the members of these families, supporting the probable contribution of undetermined exogenous factors in the susceptibility to SSc 8 …”
supporting
confidence: 57%
See 2 more Smart Citations
“…Unexpectedly, a higher frequency of ANA in the healthy spouses of the patients (50%) and other members of both families, compared with the ANA prevalence in their first‐degree relatives (19%), was shown. Also, these results could account for the existence of environmental exposure shared by the members of these families, supporting the probable contribution of undetermined exogenous factors in the susceptibility to SSc 8 …”
supporting
confidence: 57%
“…The age of onset between siblings is typically 10 years; this fact, together with the difference in age of onset between the affected parents and children, could show that, within families, a shared environmental trigger acting on a genetic predisposition, rather than a genetic trigger, could be of importance in the development of the disease 6 . This may also be supported by the finding of a high frequency of autoantibodies in the spouses of SSc patients as well as in their relatives 6–8 …”
mentioning
confidence: 92%
See 1 more Smart Citation
“…7 Earlier familial SSc studies showed identical HLA haplotypes within families, but no shared class II MHC antigens between families. 8,9 Possibly, different antibodies and haplotypes in SSc suggest a different response to immunomodulatory therapies; this finding is supported by studies on molecular biology of SSc skin and genetic polymorphisms in other rheumatic diseases. 5,10 In conclusion, this unique report of a multicase family affecting 3 members with different autoantibodies and clinical features supports the theory that the genetic background in SSc contributes to the risk of getting SSc but does not seem to define phenotype and antibody profile.…”
Section: Three Cases Of Systemic Sclerosis Within One Family With Dif...mentioning
confidence: 97%